THE ANALYSIS OF STATEGIES IMPLEMENTED BY SURAKARTA CITY TO BE A MICE TOURISM DESTINATION POST COVID-19: ANALISIS STATEGIES KOTA SURAKARTA MENJADI TUJUAN WISATA MICE PASCA COVID-19 - Estika Paramita Sani; M . Rachman Mulyandi (Pusat Riset dan Inovasi Nasional, 2022)
Tourism is a mainstay sector in Indonesia, with Indonesia's considerable tourism potential, many types of tourism in Indonesia, one of which is MICE tourism. MICE itself is an abbreviation of Meeting, Incentive, Conference and exhibition, the target of this MICE is that MICE is convention tourism, for example, a group of people such as statesmen, scholars and others who intend to discuss issues related to their interests. One of the cities in Indonesia that has been designated as a MICE tourist location is Surakarta. This study will discuss the readiness of the city of Surakarta as an Indonesian MICE destination and will also discuss the impact of Covid-19 on MICE tourism in Surakarta City. In this study, it was found that Surakarta City continues to improve its infrastructure to support tourism and there is an increase in the number of tourists, especially MICE tourists. However, Covid-19 also has an impact on the tourism sector in Surakarta City, which is also felt by business people who support MICE tourism